Science in the nineteenth-century periodical :
Magazines and periodicals played a far greater role than books in influencing the Victorians' understanding of the new discoveries and theories in science, technology and medicine of their era. This book identifies and analyzes the presentation of science in the periodical press in Britain between 1800 and 1900.